THE ROLE OF THE KEPUL APPLICATION IN MANAGING WASTE FORMS OF SOCIAL CONSTRUCTION TECHNOLOGY IN NEW MEDIA - Handoko, M.; Mailin, Mailin; Bahri, Ahmad Fajar; Endrayani, Deni (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2022)
Technology is something that cannot be separated from the life of modern society today. Technology is here to help humans in carrying out their daily activities. Whether hummans are the creators of technology,or technology forms hummans in such a way.This question is tried to be answered by the Social Construction Theory of Technology, this theory holds that humans determine technology. Social construction is a condition where people need and make technology because it is based on their social needs. This means that humans and technology can never be separated. Humans will continue to need technology and innovate to create new technologies to facilitate all activities of human life. The presence of online cleaning service applications, as a concrete example of the implementation of technological social construction in the media bar, where online cleaning service applications such as KEPUL were created as a solution for the community to overcome the problem of houses full of used goods that are no longer suitable for use so that they make the house look grubby and bushy. With this kepul application, it will be easier and faster to sell used goods so that they make money.